Development of a duplex ddPCR assay for detection of the endangered European eels in the diet of the invasive European catfish - Castagné, Paul; Martignac, François; Santoul, Frédéric; Blanchet, Simon; Loot, Géraldine (Knowledge & Management of Aquatic Ecosystems, 2024)
International audience Digital droplet PCR (ddPCR) is an emerging and affordable method already applied to different fields and can now be used to enhance the detection of new species using DNA samples. It could be particularly useful for detecting prey DNA in stomach content or faeces of predators, which is often challenging using traditional methods. Here, we develop a ddPCR assay to detect predation events of a native endangered fish species, the European eel ( Anguilla anguilla ) from stomach content of an invasive predator, the catfish ( Silurus glanis ). We demonstrated that this technique presents a very high sensitivity (limit of detection of eel DNA in vitro: 1.5 * 10 −3 ng/μL), a good linearity and reproducibility. Then, ddPCR allowed us to identify the presence of eel DNA in the stomach contents of 7 catfish out of the 32 catfish specimens we analyzed, whereas the traditional morphological identification approach detected only one predation event. This method could contribute to a more precise understanding of trophic interactions between prey and predators.